Photodynamic and Nail Penetration Enhancing Effects of Novel Multifunctional Photosensitizers Designed for The Treatment of Onychomycosis. (25th November 2013) - Smijs, Threes; Dame, Zoë; de, Ellen; Aans, Jan‐Bonne; Pavel, Stan; Sterenborg, Henricus
Abstract Novel multifunctional photosensitizers (MFPSs), 5, 10, 15‐tris(4‐N‐methylpyridinium)‐20‐(4‐phenylthio)‐[21H, 23H]‐porphine trichloride (PORTH) and 5, 10, 15‐tris(4‐N‐methylpyridinium)‐20‐(4‐(butyramido‐methylcysteinyl)‐hydroxyphenyl)‐[21H, 23H]‐porphine trichloride (PORTHE), derived from 5, 10, 15‐Tris(4‐methylpyridinium)‐20‐phenyl‐[21H, 23H]‐porphine trichloride (Sylsens B) and designed for treatment of onychomycosis were characterized and their functionality evaluated. MFPSs should function as nail penetration enhancer and as photosensitizer for photodynamic treatment (PDT) of onychomycosis. Spectrophotometry was used to characterize MFPSs with and without 532 nm continuous‐wave 5 mW cm−2 laser light (± argon/mannitol/NaN3). Nail penetration enhancement was screened (pH 5, pH 8) using water uptake in nails and fluorescence microscopy. PDT efficacy was tested (pH 5, ± argon/mannitol/NaN3) in vitro with Trichophyton mentagrophytus microconida (532 nm, 5 mW cm−2). A light‐dependent absorbance decrease and fluorescence increase were found, PORTH being less photostable. Argon and mannitol increased PORTH and PORTHE photostability; NaN3 had no effect. PDT (0.6 J cm−2, 2 μm) showed 4.6 log kill for PORTH, 4.4 for Sylsens B and 3.2 for PORTHE (4.1 for 10 μm). Argon increased PORTHE, but decreased PORTH PDT efficacy; NaN3 increased PDT effect of both MFPSs whereas mannitol increased PDT effect of PORTHE only. Similar penetration enhancement effects were observed for PORTH (pH 5 and 8) and PORTHE (pH 8). PORTHE is more photostable, effective under low oxygen conditions and thus realistic candidate for onychomycosis PDT.